HYGIENE PERSONAL MAHASISWA PADA MATA KULIAH PASTRY DI WORKSHOP TATA BOGA JURUSAN KESEJAHTERAAN KELUARGA FT UNP - Sari, Novita; Elida, Elida; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2015)
This research aims to get an overview of personal hygiene  at Pastry  courses.  This type of research is a research survey, the population is  students  who follow the Pastry  courses  listed on the semester January-June 2015 that took the Pastry Courses  and sample  taken  through the total sampling.  Research instrument using the format of research using using two alternative  answers. Data analysis techniques by means of determining frequency distribution  data and determine the level of attainment of respondents.  Personal hygiene  in  workshops the Home Economic is good.  Personal  hygiene with sub indicators of fingers and hands well.Indicators of the head and the hair well. Indicators of clothing work clothes very well. Indicators  shoes stated very good .   Keywords: Personal Hygiene, Pastry Courses, Workshops